Rancang Bangun Alat Pemberi Makan Entok Otomatis Berbasis Internet of Thing (IoT) - Yasmin, Zahra Atharid Yasmin; Made, Made Rahmawaty; Khamdi, Nur Khamdi; Edilla, Edilla (Jurnal Elektronika dan Otomasi Industri, 2023)
A system using Internet of Things (IoT) technology has been developed to assist farmers in efficiently feeding their pet ducks. This system based on the Internet Of Things (IoT) method, involves various components such as loadcell and ultrasonic sensors, servo motors, a real-time clock, LCD display, power supply, and the NodeMCU ESP8266 microcontroller. The feeding process starts by filling the feed into a container hopper. The ultrasonic sensor detects the feed level and sends this information to the Blynk application. The application then opens servo motor 1 to drop the feed into a small container with a loadcell. The loadcell sensor measures the weight of the feed, and then servo motor 1 closes and servo motor 2 opens until the feed runs out, at which point servo motor 2 closes. The system continuously repeats this process and sends notifications to the Blynk application when the hopper is empty. Overall, this system helps to streamline the feeding process for pet ducks and improve efficiency for farmers.